Expanded Newborn Screening Using Tandem Mass Spectrometry: Seven Years of Experience in Eastern Sicily - MariaAnna Messina; Concetta Meli; Federica Raudino; Annarita Pittalá; Alessia Arena; Rita Barone; Fortunata Giuffrida; Riccardo Iacobacci; Vera Muccilli; Giovanni Sorge; Agata Fiumara (MDPI AG, 2018)
The expanded newborn screening for selected inborn errors of metabolism (IEM) in Sicily was introduced in 2007 by a Regional project entitled "Early detection of congenital metabolic diseases: expanded neonatal screening". It established two newborn screening laboratories, for Western and Eastern Sicily, which started their activity in 2011. Here we present the results of expanded screening (excluding phenylketonuria (PKU)) of the Eastern laboratory from January 2011 to December 2017. Our data highlight the importance of the expanded newborn screening as a basic health program to avoid the underestimation of rare diseases and the need of further investigations even when there are no textbook alterations of the metabolic profiles. We performed our analysis on dried blood spot by tandem mass spectrometry, according to Italian guidelines. A total of 196 samples from 60,408 newborns gave positive screening results (recall rate 0.32%) while 12 babies were true positive, including 2 newborns whose mothers resulted in being affected by a metabolic disease. The overall frequency of IEM found in the screening panel was 1:6041 (mothers excluded) or 1:5034 (mothers included). The introduction of MS/MS technology in Sicily has significantly increased the detection of inherited metabolic disorders, including those not previously covered, with a predictable improved outcome for several disorders.